Silent colonic perforation and enterocutaneous fistula by a ball point pen 13 years after ingestion in a patient with schizophrenia - Dheeraj Kattula; Stephen Amarjeet Jiwanmall; Balaji Srinivasa Sekaran; Somanatha Sharma (Journal of Family Medicine and Primary Care, 2018)
Patients with mental illness do not get medical and surgical attention as required. Here is a case of poor, unemployed gentleman with an ulcer which was carefully evaluated and treated appropriately. The presentation is novel in many other ways. The object of size 6 × 2.5 cm usually does not cross the duodenum, but in his case an 11-cm long pen had reached the splenic flexure. It also had stayed dormant for over 13 years before causing complications. When the pen perforated the bowel, the patient is expected to present with acute abdomen, but in this case it presented as enterocutaneus fistula. This case is first of its kind in medical literature.